Antimicrobial stewardship opportunities among inpatients with diabetic foot infections: microbiology results from a tertiary hospital multidisciplinary unit. Issue 4 (7th April 2019) - Hand, Robert; Manning, Laurens; Ritter, Jens C.; Norman, Paul; Lamb, Lydia; Makepeace, Ashley; Sankhesara, Dipen; Hamilton, Emma; Ingram, Paul
Abstract: Among 125 inpatients with diabetic foot infections managed by a multidisciplinary foot ulcer unit, knowledge of methicillin‐resistant Staphylococcus aureus colonisation status assisted decision‐making to prescribe appropriately or with‐hold empiric anti‐methicillin‐resistant Staphylococcus aureus therapy. Despite adherence to national guidelines, apparent overuse of anti‐pseudomonal therapy was frequent, providing potential antimicrobial stewardship opportunities.